Characteristics of Critical Thinking Skills of Class XI Senior High School on Stoichiometry Material - Devi, Sinta; Afadil, Afadil (Jurnal Akademika Kimia, 2023)
This study aims to describe the characteristics of students’ critical thinking skills in the Stoichiometry material of class XI SMA Negeri 1 single. This type of research is descriptive quantitative. The sample of this research was all students of class XI SMA Negeri 1 Sindue, which consisted of 3 classes, namely class XI MIA 1, XI MIA 2, and XI MIA 3. The data in this study were obtained through a test of students' critical thinking skills in the form of essays with as many as five items. Three essential thinking indicator items are interpretation, analysis, and inference. The results of data analysis for students' critical thinking skills for indicators of interpretation, analysis, and inference showed that class XI MIA 1 obtained the percentage results for the interpretation indicator 40,5 % in the low category, the analysis indicator obtained by the percentage of 35 % was included in the low category, and indicator inference obtained a percentage of 17 % who are in the very low category. Class XI MIA 2 obtained the percentage result on the interpretation indicator 46 %, which is in the low category. In comparison, the analysis indicator obtained a percentage of 59.5 % who are in the low category, and indicators inference obtained a percentage of 25,5 % who are in the low category. Whereas in class XI MIA 3, the percentage of interpretation indicators was 44 % in the low category, the analysis indicators obtained a percentage of 57,5 % who were in the low category. The inference indicator obtained 23,5 % who were in the very low category. Based on the research results at these schools, it can be seen that the critical thinking skills of class XI students of SMA Negeri 1 Sindue are still very low.